2019
DOI: 10.3390/ani9090661
|View full text |Cite
|
Sign up to set email alerts
|

Local Dot Motion, Not Global Configuration, Determines Dogs’ Preference for Point-Light Displays

Abstract: Simple SummaryAnimal motion is characterised by predictable kinematics according to their body morphology and the laws of gravity. This pattern of movement, called biological motion, is traditionally studied using animated displays created by placing a small number of light dots on the major joints of living beings. Previous studies have shown that several animal species can reliably discriminate dot displays depicting an animal walking, and their performance is impeded when the display is turned upside-down a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 52 publications
3
25
1
Order By: Relevance
“…Other non‐human animals tested with conspecific‐shaped PLFs using discrimination tasks, including visual search tasks, include pigeons (Dittrich, Lea, Barrett, & Gurr, 1998; Qadri, Asen, & Cook, 2014; Troje & Aust, 2013; Watanabe & Troje, 2006; Yamamoto, Goto, & Watanabe, 2015), chimpanzees (Tomonaga, 2001), baboons (Parron, Deruelle, & Fagot, 2007) and rats (MacKinnon, Troje, & Dringenberg, 2010). Second, research has also used methods that study animals' spontaneous preference for certain types of PLFs, testing approaching behaviour in chicks (Regolin, Tommasi, & Vallortigara, 2000; Vallortigara, Regolin, & Marconato, 2005; Yamaguchi & Fujita, 1999) and quails (Yamaguchi & Fujita, 1999) and preferential looking in marmosets (Brown, Kaplan, Rogers, & Vallortigara, 2010) and in dogs (Eatherington, Marinelli, Lõoke, Battaglini, & Mongillo, 2019; Ishikawa, Mills, Willmott, Mullineaux, & Guo, 2018; Kovács et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other non‐human animals tested with conspecific‐shaped PLFs using discrimination tasks, including visual search tasks, include pigeons (Dittrich, Lea, Barrett, & Gurr, 1998; Qadri, Asen, & Cook, 2014; Troje & Aust, 2013; Watanabe & Troje, 2006; Yamamoto, Goto, & Watanabe, 2015), chimpanzees (Tomonaga, 2001), baboons (Parron, Deruelle, & Fagot, 2007) and rats (MacKinnon, Troje, & Dringenberg, 2010). Second, research has also used methods that study animals' spontaneous preference for certain types of PLFs, testing approaching behaviour in chicks (Regolin, Tommasi, & Vallortigara, 2000; Vallortigara, Regolin, & Marconato, 2005; Yamaguchi & Fujita, 1999) and quails (Yamaguchi & Fujita, 1999) and preferential looking in marmosets (Brown, Kaplan, Rogers, & Vallortigara, 2010) and in dogs (Eatherington, Marinelli, Lõoke, Battaglini, & Mongillo, 2019; Ishikawa, Mills, Willmott, Mullineaux, & Guo, 2018; Kovács et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, no such effect of scrambling but an effect of inversion was found on approaching preference in chicks (Vallortigara & Regolin, 2006). Second, some of the above studies concluded that animals were capable of detecting biological motion in PLFs (Brown et al, 2010; Dittrich et al, 1998; Ishikawa et al, 2018; Kovács et al, 2016; Regolin et al, 2000; Troje & Aust, 2013; Vallortigara et al, 2005; Watanabe & Troje, 2006; Yamaguchi & Fujita, 1999), whereas others reported negative results and stated that the positive findings of animals recognising biological motion in PLFs may be due to animals using certain configurational properties of the PLF, that is paying attention to sub‐configurations of the dots rather than perceiving the PLF stimulus as a whole representing conspecifics (Eatherington et al, 2019; Parron et al, 2007; Qadri et al, 2014; Tomonaga, 2001; Yamamoto et al, 2015). In particular, when animals gain food or are reinforced during repeated training occasions, they have the chance to learn about configurational properties of PLFs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations